Oral Squamous Cell Carcinoma with Lymph Node Metastasis in a 12 Years-Old Sphynx Female Cat - Hatipoglu, Fatih; Tas, Abuzer; Bozkurt, M. Fatih; Risvanli, Ali; Sen, Ismail (Selcuk Univ Press, 2024)
In this report, a case of oral squamous cell carcinoma (OSCC) with lymph node metastasis was described in a 12 years-old Sphynx female cat. The mandibular lymph node was totally removed and dissected (lymphadenectomy). The oral necrotic-ulcerated mass was extirpated. In the oral mass, pleomorphic squamous epithelial cells with atypical cellular features, erosions and ulcers were also observed. Squamous epithelial cells with prominent atypical cell features were found in the mandibular lymph node. Immunohistochemical examination revealed that neoplastic cells were positive for AE1-AE3 and cytokeratin 5/6. It was found appropriate to present the case in order to draw attention to the fact that dogs and cats with chronic gingivostomatitis with erosions and ulcers on the oral mucosa should also be evaluated in terms of OSCC.
Sfenks Irkı 12 Yaşındaki Dişi Bir Kedide Lenf Nodu Metastazlı Oral Yassı Hücreli Karsinom